PENGARUHPENGGUNAAN MODEL CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR DASAR LISTRIK ELEKTRONIKA SISWA KELAS X TEKNIK AUDIO VIDEO (TAV) SMK NEGERI 5 PADANG - Palupi Palupi; Nelda Azhar; Almasri Almasri (Universitas Negeri Padang, 2018)
The problem in this study is the low average learning outcomes of students on subjects Applying Electric and Electronics Engineering Basics is under the Minimum Criterion of completeness (KKM) which has been established SMKN 5 Padang is 75. This study aims to determine the effect of application of learning models Contextual Teaching & Learning and Problem Base Learning model on student learning outcomes on subjects Applying Electric and Electronics EngineeringBasics of students Audio Video Techniques at SMKN 5 Padang 2017/2018. The type of this research is experimental research with Pre experimental design with NonProbability Sampling design. The sample of research is class 1E 1B as experiment class using Contextual Teaching & Learningmodel and class 1E 1A as control class using Problem Base Learning model. Data collection techniques from post-test in the experimental class and control class, then analyzed for homogeneity test, normality test and hypothesis test. From the experimental class research results obtained an average value of 82.47, while the control class gets an average value of 77.88 with more influence6 %. The result of hypothesis calculation at significant level α = 0,05 got count> ttable that is 2,869>1,696, because big count of ttable, null hypothesis (Ho) rejected and alternative hypothesis (Ha) accepted. Can be concluded mean at the real level, this research shows that, there is influence of student learning result which signifikan between usage model ofContextual Teaching & Learning type with Problem Base Learning model on subjects Applying Electric and Electronics Engineering Basics of student of Audio Video Technique at SMKN 5 Padang. So the Contextual Teaching & Learninglearning model is gives better than results to the Problem Base Learning.Keywords : Learning outcomes, Model of Learning,Contextual Teaching & Learning, Problem Base Learning.